Pyridostigmine induced heart block requiring ICU admission - Benjamin Chaucer; Dustin Whelan; Dronacharya Lamichhane (Greater Baltimore Medical Center, 2018)
Myasthenia gravis is an autoimmune disorder that effects an estimated 20 people per 100,000 in the USA per year. Pyridostigmine is a common drug used in the symptomatic treatment of myasthenia gravis. While generally safe and effective, a rare set of patients treated with pyridostigmine encounter cardiac conduction disorders. Here, we report a rare presentation of an adverse drug reaction due to pyridostigmine, which is important for its implications in the acute care setting.